Relevansi Perjanjian Kerja Dalam UU No. 13 Tahun 2003 Tentang Ketenagakerjaan Dengan Hukum Islam - Saifudin Saifudin (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
Manpower has a role, a very important position as a national development agent and target. The work agreement in Islamic law is included in the ijarah al amal contract, meaning that the contract of sale and purchase of benefits in the form of work. This study discusses the relevance of work agreements in Law No. 13 of 2003 concerning employment with Islamic law, namely the concept of al-ijarah al-akad contract. After collecting the data and analyzing it, the analysis results show the relevance of the work agreement in Law No. 13 of 2003 concerning manpower with Islamic law in the Ijarah contract in terms of: legal conditions of employment agreement, elements in the work agreement, the period of the agreement and the expiration of the work agreement. All show the relevance of the employment agreement in Law No. 13 of 2003 concerning employment with Islamic law, namely the concept of al-ijarah al-akad contract.